VD_FINDINFO HC / 2025 / 924 vom 20. November 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 ch. 1 CC, 285 CC, 279 CPC (CH)